Inhalation therapy in elderly patients - Pirożyński, Michał (Przewodnik Lekarza/Guide for GPs, 2010)
Inhalation therapy is the most important therapeutical modality in treatment of chronic respiratory disorders. Starting inhalation therapy in elderly patients one must keep in mind the differences in physiology of the respiratory tract seen in this of patients, which can hamper inhalation. The observed differences in senile patients may influence the penetration of aerosol particles and effect deposition rates. The elderly due to concomitant disorders may experience problems with the correct use of individual inhalers thus all inhalator methods should be assessed in this group of patients before starting therapy. The article discusses the use of pMDI, DPI and nebulizers in the elderly patients.